1992
DOI: 10.2337/diab.41.11.1491
|View full text |Cite
|
Sign up to set email alerts
|

1,25-Dihydroxyvitamin D3 Prevents Insulitis in NOD Mice

Abstract: The active form of vitamin D, 1,25(OH)2D3, can prevent various forms of experimentally induced autoimmune disorders. The aim of this study was to confirm these findings in NOD mice that spontaneously develop an autoimmune type of diabetes mellitus. Therefore, the effect of a long-term 1,25(OH)2D3 treatment on the incidence of insulitis, the histological lesion preceding diabetes, was studied. Forty-three NOD mice were treated with 1,25(OH)2D3 (5 micrograms/kg) i.p. every other day from age 21 days on, when no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
119
0
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(124 citation statements)
references
References 29 publications
2
119
0
2
Order By: Relevance
“…The influence of 1␣,25(OH) 2 D 3 on immune function has been the subject of numerous reports (13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Direct modulation of T cells and macrophage͞monocytes by 1␣,25(OH) 2 D 3 has been documented in vitro (13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…The influence of 1␣,25(OH) 2 D 3 on immune function has been the subject of numerous reports (13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Direct modulation of T cells and macrophage͞monocytes by 1␣,25(OH) 2 D 3 has been documented in vitro (13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…Pancreases from all experimental groups at 100 and 250 days were embedded in optimal cutting temperature (OCT) medium, snap-frozen in 2-methyl-butane 99% + chilled in liquid nitrogen and stored at −80°C until processing [20]. 5-µm cryostat sections were stained with Mayer's haematoxylin and eosin.…”
Section: Histologymentioning
confidence: 99%
“…The active form of vitamin D (1,25 dihydroxyvitamin D3) inhibits T cell proliferation and suppresses both tumour necrosis factor a (TNFa) and interleukin-1 production [24]. Furthermore, in the NOD mouse (an excellent animal model of IDDM) vitamin D3 administration prevents the development of IDDM as well as the associated autoimmune insulitis [25]. In a recent study in Bangladeshi subjects living in east London, vitamin D levels were found to be reduced in those most at risk for non-insulin-dependent diabetes [26].…”
mentioning
confidence: 99%